2008
DOI: 10.1088/0022-3727/42/2/025101
|View full text |Cite
|
Sign up to set email alerts
|

Temperature performance of terahertz quantum-cascade lasers: experiment versus simulation

Abstract: We report the electrical and the optical characteristics of 2 THz quantum-cascade lasers with a similar four-well resonant-phonon design. A Monte Carlo simulation, employed to evaluate the temperature performance of the device, indicates that the degradation of material gain with increasing temperature is attributed to the rapid decrease in the lifetime of the upper lasing level and the relatively stable lifetime of the lower lasing level. Because of the broadening effect of the temperature dependent gain prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Combining versatility and reliability with relative computational efficiency, the EMC approach has been widely used for the analysis, design and optimization of QCLs. 46,47,[99][100][101][102][103][104][105][106][107][108][109][110] In both the rate equation and EMC approach, the carrier transport is described by scattering-induced transitions of discrete electrons between the quantized energy levels, corresponding to a hopping transport model. Such methods are referred to as semiclassical, since the energy quantization in the QCL heterostructure is considered, but quantum coherence effects and quantum mechanical dephasing are not included.…”
Section: Overview and Classification Of Carrier Transport Modelsmentioning
confidence: 99%
“…Combining versatility and reliability with relative computational efficiency, the EMC approach has been widely used for the analysis, design and optimization of QCLs. 46,47,[99][100][101][102][103][104][105][106][107][108][109][110] In both the rate equation and EMC approach, the carrier transport is described by scattering-induced transitions of discrete electrons between the quantized energy levels, corresponding to a hopping transport model. Such methods are referred to as semiclassical, since the energy quantization in the QCL heterostructure is considered, but quantum coherence effects and quantum mechanical dephasing are not included.…”
Section: Overview and Classification Of Carrier Transport Modelsmentioning
confidence: 99%
“…In the last decade, significant scientific effort has been directed towards identifying the main temperaturedegrading mechanisms [5][6][7][8] , as well as finding optimized QCL designs [9][10][11][12][13][14] . The degrading mechanisms include thermal backfilling 3,15 , thermally activated LO phonon emission [6][7][8]16 , increased broadening [17][18][19] , and carrier leakage into continuum states 20 . When numerically optimizing a design, it is important to take all of these effects into consideration, in order to ensure a close correspondence between the model and the real device.…”
mentioning
confidence: 99%
“…We would like to note that, as Li et al (2009b) demonstrated, the calculations of gain peak require to account for changes of Dm with temperature. Only when Dm broadening with increase of temperature had been included, the agreement with experimental results has been achieved.…”
Section: Optical Gainmentioning
confidence: 94%
“…Temperature performance and limiting factors for high temperature operation of various designs of THz QCL have been addressed in multiple reports (Jirauschek and Lugli 2008a, b;Li et al 2009b;Mátyás et al 2010a;Cao 2010, 2012).…”
Section: Examples Of MC Studies Of Qclmentioning
confidence: 99%